Establishment of Causal Attribution as A Regulatory Strategy for Teaching and Learning - Maziane Brahim; Belaaouad Said; Benmokhtar Said (Iraqi Journal of Science, 2021)
The theme of causal attribution has generated a great deal of work and focuses on the factors to which people attribute their behavior. However, its use to explain the results of the evaluation and the support for the regulation of teaching and learning acts has rarely been raised. Indeed, in the evaluation act, which is a privileged moment for reframing the learning process, teachers attribute the results obtained to the student himself, without worrying about the factors to which the student attribute itself these failures. This can distort the regulatory process and increase failure factors. The teacher's attributions of failure often relate to the results of the evaluations and are often explained by factors external to him: such as the lack of commitment of the students, their incompetence and their degree of understanding. and these are internal factors for the student. The aim of this presentation is to show that: the regulation of the teaching and learning act should not only focus on the results of the evaluation but also on the factors to which the student himself attributes his own failure. Involving the student in the teaching act must also involve his involvement in the evaluation and regulation process.